Revisiting Postoperative Vision Loss following Non-Ocular Surgery: A Short Review of Etiology and Legal Considerations - Mendel, Ehud; Stoicea, Nicoleta; Rao, Rahul; Niermeyer, Weston; Revilla, Stephen; Cluse, Marcus; Sandhu, Gurneet; Todaro, Gerald J.; Bergese, Sergio D. (Frontiers in Surgery, 2017)
Postoperative vision loss (POVL) following nonocular surgery is a serious complication where the causes are not fully understood. Studies have identified several causes of POVL as well as risk factors and prevention strategies. POVL research is made difficult by the fact that cases are often subject to malpractice claims, resulting in a lack of public access to case reports. This literature review was conducted in order to identify legal issues as a major barrier to studying POVL and address how this affects current knowledge. Informed consent provides an opportunity to overcome legal challenges by reducing malpractice litigation through educating the patient on this outcome. Providing pertinent information regarding POVL during the informed consent process has potential to reduce malpractice claims and increase available clinical information.